INTEGRASI PENGUNGSI ASING DENGAN MASYARAKAT DI KOTA PEKANBARU - Haniva Sekar Deanty; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research analyses the existence of refugees in Indonesia, particularly in the city of Pekanbaru. This issue is interesting because more refugees are stranded in a transit country like Indonesia as third countries have stricted their immigration policy and resettlement program for refugees. Even though Indonesia acceptances of refugees arrival has been based on humanity considerations, Indonesia itself is not a state party to the 1951 Refugee Convention nor its 1967 Protocol. Thus Indonesia does not have the obligations to follow the rules and duties to provide the refugees’ basic rights, such as the right to get an education or getting a job.This research adopts Karen Jacobsen’s local integration theory, in which she said that the integration will be considered successful if the society in asylum country accepts the existence of the refugees. Information regarding this topic was collected through interviews with respondents such as the officials from the local government and RUDENIM; the staffs from international organizations like UNHCR and IOM; NGOs; the local citizen; and the refugee themselves.This research shows that there have been progress on how refugees are treated in Indonesia, especially with the adoption of the President Regulation Number 125 Year 2016. The city of Pekanbaru has also allowed child refugees to access primary education in the city. In terms of integration, however, there is more to be done. The people of Pekanbaru are aware and accept the refugees living among them even though there were some resistance at the beginning. Some people feared that the cultural differences between the refugees and the locals could affected the society. While some refugees have maintained social contacts with the locals, an indication that there have been some informal of integration, they have lamented that they are prohibited to get a job or to access higher education. Keywords: refugees, human rights, local integration, The 1951 Refugee Convention, President Regulation Number 125 Year 2016.